Susceptibility of Nigerian West African Dwarf and Red Sokoto goats to a strain of Trypanosoma congolense - Adah, M.I.; Otesile, E.B.; Joshua, R.A. (Elsevier, 1993)
West African Dwarf (WAD) and Red Sokoto (RS) goats were experimentally infected with the Kafanchan strain of Trypanosoma congolense and the course of the infection was monitored. The organism was pathogenic and produced fatal disease in the goats, which was characterized by rapid progressive anaemia, leucocytosis, weight loss and death. All RS goats died within 11 days of infection, and had a mean reduction in packed cell volume (PCV) of 11 %. In West African Dwarf goats, one death occurred on Day 13 post-infection with a mean drop in PCV of 9%. Statistically significant (P